(untitled) (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Paediatric surgical cases has been operated by general surgeon due to lack of paediatric surgeons. Complex cases in neonates and infants is being referred to other centres with paediatric surgical services. This study aims to compare the spectrum of paediatric surgical cases and their outcome before and after availability of paediatric surgeon. Method: This is the Retrospective study conducted at Patan Academy of Health Sciences over a period of 4 years. Group 1 included surgeries during 1st 2 y before and Group 2 during 2nd 2 y period after the availability of paediatric surgeon. Ethical approval was obtained. Patient age, sex, diagnosis, operative procedure, type of surgery and outcome data were collected from operative theater register and patients file from medical record section. Data analysis was done using SPSS 16. Result: Among 1157 cases, 369 cases were in group 1 and 788 in group 2. Male to female ratio was 2.8:1. Laparotomy 270(23.2%) was the most performed inpatient surgery and hernitomy 221(19.1%) in day care. There was total 52(4.5%) neonates, 2(4%) in group 1 and 50(96%) neonates in group 2. Among total cases mortality rate was 8(0.7%) in group 2, due to preterm birth, delayed presentation and septicemia. Conclusion: Lower GI tract and skin and soft tissue were most common system involved. Laparotomy and incision and drainage were most performed surgery before and after availability of paediatric surgeon. There was 96% increment in neonatal cases (50 v/s 2) after availability of paediatric surgeon. Mortality was 8(0.7%) in group-2 due to delayed presentation and septicemia.